Response speed measurements on the psychomotor vigilance test: how precise is precise enough?. Issue 1 (2nd July 2020) - Basner, Mathias; Moore, Tyler M; Nasrini, Jad; Gur, Ruben C; Dinges, David F
Abstract: Study Objectives: The psychomotor vigilance test (PVT) is frequently used to measure behavioral alertness in sleep research on various software and hardware platforms. In contrast to many other cognitive tests, PVT response time (RT) shifts of a few milliseconds can be meaningful. It is, therefore, important to use calibrated systems, but calibration standards are currently missing. This study investigated the influence of system latency bias and its variability on two frequently used PVT performance metrics, attentional lapses (RTs ≥500 ms) and response speed, in sleep-deprived and alert participants. Methods: PVT data from one acute total ( N = 31 participants) and one chronic partial ( N = 43 participants) sleep deprivation protocol were the basis for simulations in which response bias (±15 ms) and its variability (0–50 ms) were systematically varied and transgressions of predefined thresholds (i.e. ±1 for lapses, ±0.1/s for response speed) recorded. Results: Both increasing bias and its variability caused deviations from true scores that were higher for the number of lapses in sleep-deprived participants and for response speed in alert participants. Threshold transgressions were typically rare (i.e. <5%) if system latency bias was less than ±5 ms and its standard deviation was ≤10 ms. Conclusions: A bias of ±5 ms with a standard deviation of ≤10 ms could be considered maximally allowable margins for calibrating PVT systems for timing accuracy. Future studies should report the average system latency and its standard deviation in addition to adhering to published standards for administering and analyzing the PVT.